Defect Detection and Health Monitoring of Steel Structure based on UAV Integrated with Image Processing System. Issue 5 (March 2019) - Chen, Qingcheng; Wen, Xiang; Wu, Fengqi; Yang, Yuqing
Abstract: This paper presents a novel solution for defect detection and health monitoring of steel structure by involving effective use of Unmanned Aerial Vehicle (UAV) and Image Processing System. Lots of the traditional test work depends on manual labor despite that the inspection and testing environment is rather harsh. The conventional inspection method does not meet the requirements of high efficiency comprehensive security. The proposed system integrates six-axis UAV platform, image processing and big data analysis for detection and safety evaluation of steel structure's surface degradation. The visual sensor, ultrasonic sensor, laser sensor, and other complementary sensors are crossed integration for UAV platform in order to achieve stable and high-definition aerial photography, which can definitely enhance the reliability and stability of the UAV system and intelligent image processing algorithm has been applied to identify the defect and potential diseases of steel structure. Finally, the results show this approach is the cost-effective and time-compressing solution for health monitoring of steel structure.